Early identification and influence range division method of collapse hazards based on UAV oblique photography technology - Quanru Lü; Bin Zeng; Xiaojun Meng; Gang Chen; Jiakang Yan (地质科技通报, 2021)
High-level rock collapse is concealed, sudden and catastrophic. Traditional contact survey methods cannot fully guarantee the safety and also difficult to thoroughly identify the spatial distribution and development characteristics of the dangerous rock blocks on the slope. Therefore, how to obtain the key geological information on the slope surface safely, quickly and accurately has always been one of the difficulties in the investigation and evaluation of collapse disasters, and it is also an extremely important link in the disaster prevention and reduction work. Taking a high-steep rock slope in mining area in Lianyungang City as an example, the paper presents a method for early identification and influence range division of collapse hazard based on UAV oblique photography technology. The method obtains high-resolution image in the research area and constructs a high-precision geological model by oblique photography technology, uses line measurement method to extract and statistics the spatial spreading characteristics and related parameters of the dominant structure surfaces in the slope, determines instability mode of critical dangerous rock blocks in the slope by stereographic projection method, uses Rocfall to simulate the rolling motion characteristics of the collapse blocks under the worst condition after completing the stability evaluation and classification of the dangerous rock blocks, and finally the influence range of different levels was divided for disaster prevention and control. The research results show that the UAV oblique photography technology has significant feasibility and superiority in early identification, failure mode analysis, stability assessment and influence range delineation of collapse hazard. The method of early identification and influence range division of collapse hazards based on UAV oblique photography technology has important reference value.